Upaya Peningkatan Indeks Keandalan Sistem Pembangkit Dengan Peningkatan Kapasitas Sistem Pembangkit - Ulil Albab; Dian Yayan Sukma (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The reliability of electric power system generation is a very important aspect of operation electrical power system because in operation of the plant that has been scheduled is not always able tooperate in accordance with the predetermined scheduling, there are have a lot of obtacles that can cause that plant will be fail to operate properly, both due to interference from outside and fromwithin generating system itself. Through probability value of the electric power system, it is obtained how much the continuity of operation from that power plant system with good quality.That is why reliability of the power system generation must maintain the value. In this article the calculation in finding the level of reliability of the generating system uses the recursive method ofconvolution which in this case is used to find the level of reliability of a private power plant system that exists in Riau Province. Analysis conducted using data for the last 5 years by taking thereliability index is Loss of Load Expectation (LOLE). Calculation in finding the reliability index of the generator system using software MATLAB and Microsoft Excel. In the search for reliabilityindexes at the generating system, it refers to international standard for the LOLE index itself, which is 0.1 days / year.Keywords : LOLE, Power System Generation, Reliability